The Effect of Microwave Radiation on Prickly Paddy Melon (Cucumis myriocarpus) - Graham Brodie; Carmel Ryan; Carmel Lancaster (International Journal of Agronomy)
The growing list of herbicide-resistant biotypes and environmental concerns about chemical use has prompted interest in alternative methods of managing weeds. This study explored the effect of microwave energy on paddy melon (Cucumis myriocarpus) plants, fruits, and seeds. Microwave treatment killed paddy melon plants and seeds. Stem rupture due to internal steam explosions often occurred after the first few seconds of microwave treatment when a small aperture antenna was used to apply the microwave energy. The half lethal microwave energy dose for plants was 145 J/cm2; however, a dose of at least 422 J/cm2 was needed to kill seeds. This study demonstrated that a strategic burst of intense microwave energy, focused onto the stem of the plant is as effective as applying microwave energy to the whole plant, but uses much less energy.